Citizen-science Supplements Species Inventories and Reveals the Invasion of Monomorium exiguum and Pheidole parva (Hymenoptera: Formicidae) in Cyprus - Jakovos Demetriou; Lech Borowiec; Christos Georgiadis; Evan P. Economo; Helen E. Roy; Angeliki F. Martinou; Sebastian Salata (Sociobiology, 2025)
Citizen science has become more popular over the past few decades, aided by advancements in smartphone technologies and web platforms to build a community. Nevertheless, taxa that are difficult to identify and/or minute in size are often neglected. In this study, students of the rural Asomatos primary school (Limassol, Cyprus) were given ant collection kits and asked to collect specimens inside their houses within one or two weeks from the 3rd to the 16th of November 2023. Upon inspection, the native Lepisiota cf. nigra and Tetramorium schmidti Forel, 1904 are recorded for the first time from the island. A single peculiar specimen of Pheidole Westwood, 1839, was recorded indoors next to a plant nursery. As such, the plant nursery was surveyed, providing additional samples identified as Pheidole parva Mayr, 1865. Specimens from Cyprus previously identified as Pheidole fadli Sharaf, 2007, were re-examined, assigning them to P. parva. Additionally, a single specimen of Monomorium exiguum Forel, 1894 was also collected. Both alien species were most probably introduced through the horticultural pathway. This article presents the first records of the alien M. exiguum and P. parva from the island, correcting previous records and highlighting the importance of citizen science in detecting and mapping the distribution of alien and native species.